Effectiveness of non-pharmacological traditional Chinese medicine combined with conventional therapy in treating fibromyalgia: a systematic review and meta-analysis - Cai, Lili; Chen, Zhengquan; Liang, Juping; Song, Yuanyuan; Yu, Hong; Zhu, Jiaye; Wu, Qikai; Zhou, Xuan; Du, Qing (Frontiers in Neuroscience, 2023)
Objective. Fibromyalgia is a psychosomatic disorder characterized by generalized pain, which is also known as “muscular rheumatism” in Chinese medicine. We undertook this systematic review to evaluate the effectiveness of non-pharmacological traditional Chinese medicine (TCM) combined with conventional therapy on pain, health status, depression, and the life quality of patients with fibromyalgia. Methods. Studies were retrieved from five electronic databases (PubMed, the Cumulative Index to Nursing and Allied Health, Cochrane Library, Embase, and Web of Science) with publication date up to August 2022. We included randomized controlled trials examining the effects of a combination of non-pharmacological TCM and conventional therapy on pain intensity, health status, depression, and life quality. Results. Four randomized controlled trials (384 patients) met the inclusion criteria. Results of our meta-analysis indicated that non-pharmacological TCM combined with conventional therapy exerts significant positive effects on alleviating pain at the post-intervention time point than conventional therapy only (visual analog scale WMD1=-1.410, P < 0.01; the number of tender points WMD2=-2.880, P < 0.001; pressure pain threshold WMD3=0.830, P < 0.001, respectively). Significant differences in pain assessment were also observed between the two groups after a long-term follow-up (12 months) (WMD1=-1.040, WMD2=-1.620, and WMD3=0.380, all P<0.05.) The combination therapy group also showed a greater reduction in FIQ than the control group after a long-term follow-up (WMD=-6.690, P < 0.05). Depression and pain-related quality of life showed no difference between groups (all P>0.05). Conclusion. Non-pharmacological TCM combined with conventional therapy may be more effective in alleviating pain and improving the health status than conventional therapy only. However, it remains some concerns over the safety and clinic application.